Intraoral plasmablastic non-hodgkin's lymphoma associated with human immunodeficiency virus - Vijeev Vasudevan; Yella Ravi Kumar; Prathyusha Chavva; S Naina (Wolters Kluwer Medknow Publications, 2016)
Plasmablastic Lymphoma of oral cavity is an aggressive rare form of Non Hodgkin's Lymphoma which is an Acquired Immuno Deficiency Syndrome defining condition. Head and neck region is the second most common area for extranodal NHL's primarily involving gingiva and palate, which often presents as a diagnostic problem. We report a case of PBL in a 19 year old female patient later diagnosed as Human Immunodeficiency Virus (HIV) positive. She presented with expanding painful ulceroproliferative lesion involving left mandible and gingiva of 20 days duration. Histopathological examination and immunohistochemical analysis confirmed the diagnosis. Uncommon discovery of multiple bony lesions in whole body CT and hypercalcemia raise a question about Multiple Myeloma (MM). Literature showed very few cases with osteolytic lesions and none of the cases reported multiple bone lesions in skull. Our case report stresses the importance of differentiating this extremely rare case of PBL with skull lesions from MM.